Physical and electrical failure analysis of Cu/low k interconnect system - Lau, Fu Long. (2011)
Time-dependent dielectric breakdown (TDDB) is becoming one of the main reliability issues of Cu/low-k interconnect. In the study of TDDB breakdown mechanisms, a non-conventional single terminated tip test structure that provides easier failure site identification has been used. A new single terminated tip test structure with different areas, reduced line to line spacing and lower dielectric constant was developed to allow more in-depth understanding of TDDB. This project focused on the study of failure characterization of the new test structure, effect of area on breakdown voltage, conduction mechanism and TDDB. Electrical failure characterization consists of voltage ramp tests which are being used to determine the breakdown voltage and conduction mechanism. On the other hand, TDDB can be studied by constant electrical field stressing. The results showed that the conduction mechanism and TDDB are indeed affected by the area effect but has little significance on the breakdown voltage. For TDDB, failure modes 1 and 2 are identified as the source to hard breakdown. In failure mode 1, it follows the typical breakdown trend of a current decay with time followed by an abrupt increase in current. However, failure mode 2 follows a trend of current increasing with time till breakdown.